(3CYjGf GdYUQ hCYhGf GdfUQs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3Ydi Hf YjSi Hf SdjeGf Hf QeVGf Hf CHj GdcQe s
(3BNQgG (B:s
(3GdCdbGH hGdCfSGH (B: (3GHf CHj GdYHS HOQ GdOjf Hf YHO Gddg Hf GdMSjf s
(3GdfSNI HgG MhGTs
(3YdjgG SeGY GdfhQ GdOjf CHj HcQ CMeO Hf eMeO Hf Ydi Hf CHj GdaJM GdefPQi GdMfai GHf GdebUhU hLeGYI BNQjfs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
Keywords: (3GdJGQjNs